SPECIFICS OF THE HISTORICAL MEMORY OF THE POPULATION OF EASTERN UKRAINE IN THE TIMES OF THE RUSSIAN FULL-SCALE INVASION OF UKRAINE (Південний архів (історичні науки), 2024)
The study aims to analyse the specifics of the residents of eastern Ukraine's historical memory in the second year of Russia's full-scale aggression against Ukraine (2023). Research methods. Accordingly, the research methods are determined by the peculiarities of the study's source base. It is based on the data of sociological surveys of the state of historical memory and socio-political attitudes of the population. Also, the analysis is based on the specifics of the East of Ukraine as a historical and geographical region – understanding the East as a set of objective and subjective geopolitical, historical, natural and environmental, socio-political and socio-economic factors in a certain socio-historical time and selfidentification of the population. Results of the study. The study's main results can be defined as a kind of parallelogram consisting of all-Ukrainian trends of accelerated formation of modern historical memory based on an understanding of the experience of Ukrainian history, assimilation of European and universal values, and getting rid of Russian and Soviet myths. At the same time, the construction of historical memory in the East is not without features of misunderstanding the trajectory of Ukraine's historical development and its entry into the Euro-Atlantic civilisation space as a condition for the survival of Ukraine and Ukrainians. Conclusions. The author concludes that the victory in the war with Russia is the key to further shaping the modern historical memory of the population of eastern Ukraine. State institutions, local self-government and the public, should properly build their activities in the field of historical memory policy in the region.
Keywords: politics of historical memory, eastern Ukraine, Donbas, Kharkiv region, frontline, local history.